2021
DOI: 10.17344/acsi.2021.6679
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Conditions of Bioactive Compounds by Ultrasonic-Assisted Extraction from Artichoke Wastes

Abstract: In this study, bioactive compounds were extracted by ultrasonic-assisted extraction and classical extraction processes using distilled water as solvent from artichoke leaves which are considered as agricultural wastes. Antioxidant capacity, total phenolic and total flavonoid content values of the obtained bioactive extracts were determined, and extraction yields and times were evaluated to compare the extraction processes. Also, the optimum extraction conditions of ultrasonic-assisted extraction (extraction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…By setting a water-based extraction protocol, Garcia-Castello et al [ 26 ] revealed that it was possible to recover 60% of the polyphenolic quantity and 56% of antioxidant activity from the solid waste of artichoke by-products. Using ultrasound-assisted procedures, Turker et al [ 27 ] extracted a remarkable quantity of polyphenols from artichoke waste in a shorter time than traditional extraction methods. Recent advances in recovering phenolic compounds from artichoke by-products also allowed researchers to obtain phenol-enriched food products, e.g., fresh pasta [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By setting a water-based extraction protocol, Garcia-Castello et al [ 26 ] revealed that it was possible to recover 60% of the polyphenolic quantity and 56% of antioxidant activity from the solid waste of artichoke by-products. Using ultrasound-assisted procedures, Turker et al [ 27 ] extracted a remarkable quantity of polyphenols from artichoke waste in a shorter time than traditional extraction methods. Recent advances in recovering phenolic compounds from artichoke by-products also allowed researchers to obtain phenol-enriched food products, e.g., fresh pasta [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the rate of artichoke-derived waste (i.e., roots, stems, bracts, and external leaves) generated during industrial processes is around 70–85% of the plant weight [ 24 ]. Because artichoke by-products are still enriched in beneficial phenols with recognized antioxidant, antiradical, anticarcinogenic, and antiapoptotic properties, the recent literature supports the application of various methodologies involving phenolic molecule recovery [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the UAE of phenolic and flavonoid compounds from Cynara scolymus leaves (DOS, RSM, quadratic model R 2 > 0.95, and desirability function), the best conditions for obtaining a maximum yield of BC from this plant material were 20.05 min of extraction time and 65.02% of ultrasound amplitude, where the ultrasound amplitude was the most important variable [145]. Moreover, it has been reported that time (5 min), amplitude (30%), and ethanol concentration (50%) significantly influenced the extraction of phenolic compounds from wild thyme and their antioxidant properties, as demonstrated by Babotă et al [143] during the UAE process (DOD, RSM, and quadratic model R 2 = 0.95).…”
Section: D-optimal Designmentioning
confidence: 99%
“…More environmentally friendly; 3.Non-flammable, safer extraction; 4. More pollution-free to the environment; 5.Cost savings compared to organic solvents P = 500 W f = 20 kHz T = 77 °C A = 77 % [116] Olive leaves Oil P = 2.8 kW f = 20 kHz A = 80 % [117] Cinnamomum cassia bark Essential oil P = 300 W f = 25 kHz t = 35 min [118] Leaf (Sinara Sko Rems L.) Phenolic Flavonoid P = 500 W f = 20 kHz t = 20.05 min T = 25 °C A = 65.02 % [119] Coffee pills Caffeine P = 144–480 W f = 37 kHz t = 5–13 min [114] Date palm Phenolic Flavonoid f = 28, 40 kHz t = 20,40,60 min T = 30,45,60 °C [120] Olive Antioxidants (manly phenolic compounds and flavonoid) Ethanol 1. Volatile and easy to remove; 2.Easy to obtain; 3.General solubility; 4.By changing the concentration, the solvent polarity can be adjusted to meet the extraction needs of different solutes; 5.Can be recovered and reused by methods such as distillation, helping to reduce costs P = 400 W f = 24 kHz t = 15 min A = 70 % [121] Hibiscus sabdariffa calyces Anthocyanins P = 296.6 W f = 20 kHz t = 26.1 min T = 30–35 °C [122] Olive pomace Hydroxytyrosol Maslinic acid Oleanolic acid f = 60 kHz t = 5 min T = 50 °C [123] Pyrus communis ‘Starkrimson’ fruit peel Cyanidin-3-O-galactoside P = 162 W t = 11 min T = 71 °C [124] Raphanus sativus L Oil P = 165 W f = 25 kHz t = 20,40,60 min T = 30,45,60 °C ...…”
Section: Application Of Uaeementioning
confidence: 99%